Symmetric Separation of Variables for the Extended Clebsch and Manakov Models - Skrypnyk, Taras (Symmetry, Integrability and Geometry: Methods and Applications (SIGMA), 2025)
In the present paper, using a modification of the method of vector fields Z_i of the bi-Hamiltonian theory of separation of variables (SoV), we construct symmetric non-Stäckel variable separation for three-dimensional extension of the Clebsch model, which is equivalent (in the bi-Hamiltonian sense) to the system of interacting Manakov (Schottky-Frahm) and Euler tops. For the obtained symmetric SoV (contrary to the previously constructed asymmetric one), all curves of separation are the same and have genus five. It occurred that the difference between the symmetric and asymmetric cases is encoded in the different form of the vector fields Z used to construct separating polynomial. We explicitly construct coordinates and momenta of separation and Abel-type equations in the considered examples of symmetric SoV for the extended Clebsch and Manakov models.
Keywords: integrable system; separation of variables; anisotropic top